Impact assessment of effluents from fish ponds on water quality of the discharge site in the stream Strumyk Goleniowski in Zachodniopomorskie Province, north-western Poland - Bonislawska, M.; Nedzarek, A.; Rybczyk, A.; Zuk, B.; Socha, M.; Tanski, A. (Indian Journal of Fisheries, 2018)
Fish farming may have a negative impact on the environment through discharge of water containing organic matter, nitrogen and phosphorus. The paper presents the impact of effluents from the Fish Breeding and Stocking Centre (FBSC), located in Goleniowski, Zachodniopomorskie Province in north-western Poland on water quality of the discharge area in the stream Strumyk Goleniowski. FBSC uses rational methods of fish keeping and breeding. The water quality parameters of the input and output water of the centre was monitored. We identified multi-directional processes which shaped the water quality in the study sites with the main factors influencing the water quality being, temperature, alkalinity, total hardness, nutrients, ammonium nitrogen (NH3-N), total reactive phosphorus and total phosphorus. During summer season, decomposition of organic matter decreased oxygen concentration in water and during winter source of DO was diffusion. Increase in concentration of organic matter in outflow from FBSC resulted from culture as well as from primary production. Increase in concentration of NH3-N and phosphorus in outflow water resulted from released metabolites by live fish and from feed decomposition. Ammonification and nitrification influenced seasonal changes in nonorganic nitrogen forms. NH3-N and nitrate nitrogen were substantial source of nitrogen for autotrophs. The hydro-chemical conditions in the water of the FBSC should be regarded as optimum for fish that are sensitive to pollution and it did not deteriorate the quality of the outflow water.